1992
DOI: 10.1128/jcm.30.2.522-524.1992
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four techniques for detection of antibodies to cytomegalovirus

Abstract: Four serological methods were compared and evaluated for use in detecting cytomegalovirus antibody in blood and organ donors. Western blotting (immunoblotting), latex agglutination, enzyme-linked immunosorbent assay, and a recent available microparticle enzyme immunosorbent assay were used. The microparticle enzyme immunoassay appears to compare favorably with each of the other three assays tested for screening blood and organ donors for a previous cytomegalovirus infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 14 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…Active infection could result from reactivation of latent CMV infection or fresh exposure to CMV. Similar seroprevalence rates of anti-CMV IgG was reported by (Eisenfeld et al, 1992;Kraat et al, 1992;Boeke et al, 2008), which was (38%), (34%) and (35.5%) respectively however, they did not find any IgM positive cases. Although it was suggested that anti-CMV IgM positive with anti-CMV IgG+/-donation are more infectious than IgG positive and IgM negative ones but still this remain unproved (Badani, 2001).…”
Section: Antibody Positive To Both Igg Andsupporting
confidence: 82%
“…Active infection could result from reactivation of latent CMV infection or fresh exposure to CMV. Similar seroprevalence rates of anti-CMV IgG was reported by (Eisenfeld et al, 1992;Kraat et al, 1992;Boeke et al, 2008), which was (38%), (34%) and (35.5%) respectively however, they did not find any IgM positive cases. Although it was suggested that anti-CMV IgM positive with anti-CMV IgG+/-donation are more infectious than IgG positive and IgM negative ones but still this remain unproved (Badani, 2001).…”
Section: Antibody Positive To Both Igg Andsupporting
confidence: 82%
“…However, recent evaluations have clearly shown that despite their advantages in handling, serological tests need to be improved. While most immunoglobulin G (IgG)-specific assays reveal acceptable specificity and sensitivity (13), IgMspecific ELISAs are of limited use because of the high number of discordant results (18). All currently available serological assays use poorly defined natural viral antigens derived from HCMV-infected fibroblast cultures.…”
mentioning
confidence: 99%
“…Then, substrate and chromogen were added. The intensity of color developed was proportional to the concentration of anti-CMV IgM in reference standards and test samples and quantified by use of a photometric well reader at 450 nm wavelength (9) . 2.…”
Section: Methodsmentioning
confidence: 99%
“…The intensity of color developed was proportional to the concentration of anti-CMV IgG in the sample. The results were read by a micro-well reader compared in a parallel manner with calibrators and controls (9) .…”
Section: Methodsmentioning
confidence: 99%